2012
DOI: 10.1155/2012/694851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Role of Compression Stockings in Preventing Post thrombotic Syndrome: A Review of the Literature

Abstract: Background. Postthrombotic syndrome (PTS) is a burdensome and costly complication of deep vein thrombosis (DVT). Up to 50% of patients with DVT will develop the disease within two years following the diagnosis of acute DVT. Various risk factors for developing PTS have been identified and different modalities have been used to prevent its development. Compression stockings have been studied for the prevention of PTS in patients diagnosed with proximal DVT. Methods. MEDLINE and EMBASE databases were searched to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Venous hypertension, resulting from valvular reflux and residual thrombus, is implicated in the pathophysiology of PTS 2. Elastic compression stockings reduce venous hypertension and have been evaluated for the prevention of PTS; however, limitations in trial design affect the generalisability of published results 3. The study by Kahn and colleagues aims to evaluate the role of compression stockings in the prevention of PTS while addressing the methodological limitations of previously published trials.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous hypertension, resulting from valvular reflux and residual thrombus, is implicated in the pathophysiology of PTS 2. Elastic compression stockings reduce venous hypertension and have been evaluated for the prevention of PTS; however, limitations in trial design affect the generalisability of published results 3. The study by Kahn and colleagues aims to evaluate the role of compression stockings in the prevention of PTS while addressing the methodological limitations of previously published trials.…”
Section: Contextmentioning
confidence: 99%
“…These include modifying patient-specific risk factors, enhancing the time within therapeutic range and optimising duration of therapy when using anticoagulants, preventing recurrent ipsilateral DVT, and surgically intervening on venous valves 3. Although compression stockings should not be used to prevent PTS after an acute DVT, their role in treating symptoms of established PTS remains understudied and warrants further investigation.…”
Section: Commentarymentioning
confidence: 99%
“…The use of graduated compression stockings in reducing venous calliper and augmenting venous return has been investigated extensively in the literature with significant dissent on its efficacy (Byrne, 2001; Kanaan et al, 2012; MacRae et al, 2011; Partsch and Partsch, 2005). This inconsistency in results can be attributed in part to the passive nature of the compression; it is shown by Book et al (2016) that the load applied by the compression sock can differ largely across various applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to combat venous pooling, passive external compression to the lower limbs is commonly applied using graduated compression stockings (GCS). Several studies in the literature present conflicting results of the effectiveness of GCS in reducing venous calliper and augmenting venous return (Kanaan et al, 2012; Lord and Hamilton, 2004; MacRae et al, 2011; Vercruyssen et al, 2014). In Book et al (2016), it is shown that there is a large amount of variability in the applied pressure based on the leg geometry and each individual application; furthermore, it is shown that the pressure gradient from the ankle to the knee commonly did not meet the manufacturer specs (10 mmHg) even when the proper sizing protocol was followed.…”
Section: Introductionmentioning
confidence: 99%